Contraceptive counseling in 2 urban cities in Ghana and the extent of shared decision-makingAJOG Global Reports at a Glance - Raina Advani, MD; Adom Manu, PhD, MBA; Emma Edinam Kploanyi, MPH; Emmanuel Morhe, MBChB, MPH; Ernest Maya, MBChB, MPH; Sarah D. Compton, PhD, MPH (Elsevier, 2023)
BACKGROUND: Increased use of contraception is associated with reduced maternal mortality worldwide; however, an unmet need remains high in many places, including Ghana. The quality of care provided by family planning practitioners influences contraceptive use; one way to improve the quality of care is to adopt a client-centered approach to counseling, including engaging in shared decision-making. In Ghana, little is currently known about the extent of shared decision-making between clients and providers in contraceptive counseling encounters. OBJECTIVE: The purpose of this study was to explore the extent of shared decision-making during contraceptive counseling in 2 cities in Ghana. STUDY DESIGN: This was a cross-sectional study across 6 urban family planning clinics in Accra and Kumasi, Ghana. We recorded, transcribed, and analyzed 20 family planning patient-provider interactions using the "Observing PatienT InvOlvemeNt'' (OPTION) scale. This scale has 12 domains, which are scored on a 5-point scale, from 0 ("the behavior is not observed") to 4 ("the behavior is observed and executed at a high standard"); the scores of each domain are summed up for a total score ranging from 0 to 48. RESULTS: In these encounters, the mean total scores for each interaction ranged from a low of 9.25/48 to a high of 21.5/48. Although providers were thorough in sharing medical information with clients, they did not actively involve clients in the decision-making process and did not generally elicit client preferences. Across the 12 domains, the mean total score was 34.7%, which is below the 50% that would correspond with a "baseline skill level," suggesting there are very low levels of shared decision-making currently occurring. CONCLUSIONS: In these 20 patient-provider encounters, counseling was mainly a sharing of medical information from the provider with the client, without the provider eliciting information from the client about her preferences for method characteristics, side effects, or method preference. Family planning counseling in these settings would benefit from increased shared decision-making to engage patients in their contraceptive choice.